(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The report discusses the design of an 8051 based white line follower robot which accepts the commands placed along the white line and reacts accordingly. White line follower robot is an autonomous robot which once placed on a white line keeps following it. It makes use of LDRs to distinguish between contrasting light and dark coloured surfaces (in this case it is white coloured line in form of a strip over a black surface). These kind of robots find applications in many situations like in places where some materials are to be transferred from one place to another. They carry out the navigation task without human guidance as they are able to sense where to move by following the white line. This report describes a novel mechanism by which the behavior of line following robots can be altered and controlled by using external commands. These commands are themselves a pattern of white strips which are kept along the white line path of robot. Upon reading these commands robot carries out necessary actions like slowing down, turning left in next junction etc. These commands allow us to have more control on the robot and thus improves the usability. The code is written is C language using Keil as the IDE and debugger. The status of the robot while following line and accepting commands was displayed using status LEDs. The Robot was found to follow the path and take the turns accordingly along with executing the commands kept on the track.